51.5k views
3 votes
(9x2 + 10x + 4) − (9x2 + 5x − 1)

1 Answer

2 votes

For this case we must simplify the following expression:


(9x ^ 2 + 10x + 4) - (9x ^ 2 + 5x-1)

We eliminate the parentheses taking into account that:


- * + = -\\- * - = +\\9x ^ 2 + 10x + 4-9x ^ 2-5x + 1 =

We add similar terms taking into account that:

Equal signs are added and the same sign is placed.

Different signs are subtracted and the major sign is placed.


9x ^ 2-9x ^ 2 + 10x-5x + 4 + 1 =\\5x + 5

Answer:


5x + 5

User Juuro
by
4.6k points